2019
DOI: 10.1016/j.jhsg.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Wrist Arthroscopy for the Treatment of Scapholunate Predynamic Instability in the Young Active Patient

Abstract: Purpose: Predynamic instability in scapholunate (SL) ligament tears is a source of wrist pain. Despite this, identifying the proper treatment remains elusive. The purpose of this study was to evaluate return to activity after wrist arthroscopic electrothermal shrinkage for treatment of SL predynamic instability. Methods: Patients enrolled in an ongoing quality assurance project of wrist arthroscopic electrothermal shrinkage surgery for treatment of SL predynamic instability in an active duty military patient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Physicians should carefully examine the scapholunate ligament in small and occult ganglion cysts that are not clinically palpable but cause dorsal wrist pain (10). The size of the incision should give surgeons sufficient visibility and examination opportunities, and surgeons should avoid tiny incisions.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians should carefully examine the scapholunate ligament in small and occult ganglion cysts that are not clinically palpable but cause dorsal wrist pain (10). The size of the incision should give surgeons sufficient visibility and examination opportunities, and surgeons should avoid tiny incisions.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). 1 37 38 39 40 41 42 43 44 45 46 47 48 49 Substantial inter-reviewer agreement was obtained for both the title and abstract screening (κ = 0.899; 95% confidence interval [CI]: 0.874–0.923) and for full-text screening (κ = 0.777; 95% CI: 0.604–0.950). There was one level III evidence case–control study 48 and 13 level IV evidence case series studies ( Table 1 ).…”
Section: Resultsmentioning
confidence: 97%
“…The pre- and postintervention VAS pain scores were reported in four studies in the ES group (one study only reported postintervention), 37 38 39 40 three studies in the AC group (one study only reported postintervention), 42 43 44 three studies in the OC group, 45 47 49 and one study in the NT group. 1 For the ES group the postintervention VAS averaged 1.4 ± 0.5 (preintervention 5.7 ± 1.8), for the AC group the VAS averaged 3.2 ± 1.3 (preintervention 6.6 ± 0), for the OC group the VAS averaged 2.3 ± 2.1 (preintervention 5.6 ± 1.6), and for the NT group the average was 3.2 (preintervention 7.6) ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations